Sustentabilidade energética: um estudo da viabilidade econômica e financeira do uso de energia solar na avicultura - Silva, Alexandre Adilio Luiz da (2017)
The promotion of energy sustainability and the use of renewable energy sources have become a challenge to the planet. Brazil has a great advantage in having the best conditions in all its territory for the generation of clean energies, thus it seeks to improve the development of its energy matrix, which demands a restructuring, mainly in the creation of new foment policies, incentives and laws to regulate these inexhaustible sources of energy. The creation of these mechanisms should motivate the competitiveness and creation of new companies in the production of these technologies, especially solar energy, which currently involves high costs for the acquisition of equipment and facilities. In this context, the objective of this work was to perform an analysis on energy sustainability through an economic and financial feasibility study of the use of photovoltaic solar panels in poultry, and a chicken farm located in the city of Toledo-PR. In order to respond to the research problem and to meet the proposed objectives, three steps were developed in the study, the first of which refers to a survey on the environmental perception of poultry farmers in Toledo-PR, through the application of questionnaires, 66 poultry farmers in Toledo -PR, including the farmer of the studied chicken farm. After analyzing the data, it was identified that there is a potential for these poultry farmers to become ecological consumers, and that electricity is the highest cost in the poultry production process. In the second study, a proposal was presented to improve the cost management of the broiler chicken farm using the methodology developed by Embrapa Poultry and Swine by means of a control sheet. After collecting the data and all the costs of the aviaries, it was verified that the electric energy is the greater cost among the others existing in the aviaries, and that the gross revenue of the producer is negative. The third study analyzed the economic and financial viability for a farm energy sustainability project through solar energy. For this step, the Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Time were used. To conclude, the Sensitivity Analysis was carried out with three possible scenarios for the investment project. The results show that for all scenarios the project is still not feasible, and as possible causes are the high cost of acquisition of solar technology and the lack of alignment with the deadlines for financing, which make the annual parcels unsustainable the poultry activity. Although the acquisition costs of this technology are decreasing and Brazil is encouraging the use of renewable energies, there is still much to improve, starting with the public policies to encourage the use of these clean sources, especially solar photovoltaic energy in rural properties such as poultry farming that contributes so much to the Brazilian economy.